Pengetahuan Perawatan Nifas pada Masyarakat yang Terdampak Rob di Pekalongan - Ratnawati Ratnawati; Susri Utami (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:   The puerperium is the process of returning the reproductive organs to their pre-pregnancy state that requires special care. Good care is supported by good environmental conditions. The environmental situation in the affected areas has hampered sanitation and daily activities because houses have been submerged in water for a long time. This study aims to determine the knowledge of postpartum care in affected communities, especially in the area of Karangjompo village, Pekalongan Regency Methods: This article  is a descriptive study, a sample of 85 respondents postartum mother in Karangjompo Village was taken by total sampling.Results:   Knowledge of postpartum care for the affected community tidal flood in Karangjompo village is good (49.4%). However, there are still postpartum care criteria, most of which are still lacking, namely the fulfillment of sexual needs (77.6%) and the selection and use of postpartum contraceptives (67.1%).Conclusion:   There is a need for cross-sector collaboration to address various health problems, especially in maternal and child health in areas affected by tidal waves. There is a need for specific guidelines on postpartum care for people affected by rob by taking into account the material and socio-cultural aspects of the local community.